An Analysis of Speech Functions in the Victory Speech of French President Emmanuel Macron - Damanik, Haikal Yuandsyah; Manurung, Winda Azzahra; Zahara, Aqilla; Mutiara, Delfia Anggraini; Rangkuti, Linda Astuti; Zulkarnain , Iskandar (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study employs a descriptive qualitative method based on discourse analysis to examine the speech functions in French President Emmanuel Macron's victory speech, delivered on May 8, 2017. Guided by Halliday's theory of speech function, the research aimed at exploring how interpersonal meaning is realized through language in this significant political address. Data, consisting of the speech transcript was meticulously analyzed to identify patterns in mood and modality. The findings reveal a predominant use of statements, consistently realized through both full declarative clauses and declarative elliptical clauses. This dominance indicates that Macron's primary communicative purpose was to inform, assert, and establish his stance and intentions, delivering clear propositions and outlining future actions rather than engaging in direct questioning or commanding. The strategic combination of full and elliptical declaratives demonstrates Macron's articulation and his skill in structuring language for clarity and impact, ultimately conveying a resolute vision and fostering trust through declared commitments.